Effect of ZnO on preparation and properties of CaSiO3 glass–ceramics. (July 2014) - Yao, S. Y.; Wang, P.; Shao, D.; Cao, H. X.; Zhang, W. W.
<x content-type="archive" xml:space="preserve">Abstract</x> The effect of zinc oxide on the preparation and properties of wollastonite glass–ceramics has been investigated. The glass structure was studied by Fourier transform infrared (FTIR) spectra analysis, and the crystalline phases were determined by X-ray diffraction. The results showed that absorption bands of FTIR spectra shifted to low wave numbers with increasing ZnO content, which indicated reduction of the melting temperature and sintering temperature. The crystalline phases were found to change from single-phase (wollastonite) to multi-phase (wollastonite and hardystonite). Hardystonite became the dominating phase when doped with 6 wt-%ZnO. The lattice deformation of wollastonite firstly decreased and then increased with addition of ZnO. The microhardness of the batches showed the opposite trend as the lattice deformation/microhardness ratio firstly grew and then reduced. The batches with 4 wt-%ZnO had the least lattice deformation and the biggest microhardness.